Pengaruh Rebranding Logo terhadap Minat Konsumen di UMKM Warung Bu Ti di Tenggilis Mejoyo Kota Surabaya - Aqila Yusriyya Hanun; Sugito Sugito (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Tenggilis Mejoyo is one of the sub-districts in the city of Surabaya. To advance an area, there are many things that need to be considered in handling it, such as the economy of the area. The economy in Tenggilis Mejoyo Village is built on various types of economic ladder, one of which takes part is Micro, Small and Medium Enterprises. This Micro, Small and Medium Business is not free from various problems experienced, one of the aspects that is not free from problems is the branding aspect, as observed by the Village Development Team, Tenggilis Mejoyo Village, East Java